Kepemimpinan Sejati Melampaui Rasionalitas Manajerial - Ristyantoro, Rodemeus (Respons: Jurnal Etika Sosial, 2024)
Leadership and leaders are sometimes misunderstood and simply equated with rulers or officials. In fact, the terms are often used to refer to anyone holding a position within an organization or institution. While their meanings differ, there are also similarities. In general, a leader can be defined as someone who has the ability to influence others to achieve a common goal. Meanwhile, a ruler is an individual who holds authority or power to govern a region or community. Although these two roles are often associated with power, their substance differs significantly. In this paper, the author focuses more on leadership than on authority. Leadership is understood more broadly, reflecting its role in business organizations and its challenges. Furthermore, the author attempts to describe the criteria for a true leader in managing a business organization.